Numerical study of reduction in ground vibrations by using barriers. (15th May 2016) - Persson, P.; Persson, K.; Sandberg, G.
Highlights: Reduction in traffic-induced ground vibrations by using barriers was studied. Numerical investigation by means of a validated finite element model. Effects of infiltrated water was investigated, considering fluid–structure interaction. Vibration amplification occurs at long distances from the vibration source. Depth and elastic modulus were found to be the most important parameters. Abstract: Reduction in traffic-induced ground vibrations by the use of barriers is investigated. The traffic load characteristics were measured for motorway traffic. The effects of parameters on various types of barriers were examined by the use of a finite element model that was calibrated to green-field measurements. The model involved a layered soil and bedrock. The depth of a trench and the elastic modulus of a solid back-fill material were found to be the most important parameters to consider. In investigation of the effects of infiltration of water into an open trench, a coupled finite element formulation of the water and the soil was applied. Infiltration of water was found to decrease the achieved reduction. At long distances from the vibration source, of around 500 m and longer, amplification in vibration level can be seen when a trench has been installed. It was also found, at long distances, that the motion of the ground surface follows the motion of the bedrock.